Competitive grain growth behavior in laminated ceramic composites: An insight from numerical simulation. Issue 10 (15th May 2021) - Zhou, Qian; Xue, Bei; Gu, Shengyue; Yang, Zhaoning
Abstract: The properties of the laminated ceramic composites are known not only determined by the macro-laminated composite structure, but also highly dependent on their micro-polycrystalline structure. With the aim to investigate the competitive grain growth behavior during polycrystalline microstructure formation in laminated ceramic composites, a phase-field simulation for anisotropic grain growth is carried out in this study, and the effect of anisotropy in grain boundary energy on the grain coarsening and deformation near the interfaces is meticulously studied. Simulation results indicate that the polycrystalline microstructure is highly influenced by the competitive grain growth kinetics, and an oriented columnar grain layer is newly-formed near the interface. This abnormal grain growth phenomenon in the binary polycrystalline interface is attributed to the different grain boundary migrations in two layers, thereby leading to the interface migration in the laminated polycrystalline microstructures with an intermediate layer, which is consistent with experimental observations. Therefore, specifying the characteristics of the laminated polycrystalline microstructures could be an efficient way to improve the structure and performance design ability in laminated ceramics.